Mrožkov Tango in problemi njegove recepcije na Slovenskem - Troha, Gašper (Slavia Centralis, 2025)
The Problematic Reception of Tango by Slawomir Mrožek in Slovenia. The article focuses on the play Tango by t he Polish playwright Sławomir Mrozek and its fate on the Slovenian stage. Although it was staged in Belgrade and Ljubljana as early as in 1965, the same year in which it was first performed in Poland, it was later relegated to the theatrical margins. It re-entered the repertory of the Ljubljanska Drama theatre as late as in 2023. This paper analyses individual productions and critical reactions, and concludes that Josip Vidmar had a significant influence on the fate of its reception.
Keywords: Sławomir Mrožek; Tango; theatre of the absurd; Josip Vidmar; political drama